2020
DOI: 10.1021/acs.jcim.0c00661
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Pose Predictions for Human G Protein-Coupled Receptors: Insights from the Amber-Based Hybrid Molecular Mechanics/Coarse-Grained Approach

Abstract: Human G protein-coupled receptors (hGPCRs) are the most frequent targets of Food and Drug Administration (FDA)-approved drugs. Structural bioinformatics, along with molecular simulation, can support structure-based drug design targeting hGPCRs. In this context, several years ago, we developed a hybrid molecular mechanics (MM)/coarse-grained (CG) approach to predict ligand poses in low-resolution hGPCR models. The approach was based on the GROMOS96 43A1 and PRODRG united-atom force fields for the MM part. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 105 publications
0
15
0
Order By: Relevance
“…The hybrid MM/CG protocol has been successfully used to predict ligand poses in a variety of hGPCRs (Leguèbe et al, 2012;Marchiori et al, 2013;Sandal et al, 2015;Fierro et al, 2017;Capaldi et al, 2018;Fierro et al, 2019). Moreover, the Amber-based MM/CG poses improved significantly relative to those obtained by simple docking, especially for low resolution starting models (Schneider et al, 2020). However, the setup of such simulations has been time-consuming and system-dependent.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The hybrid MM/CG protocol has been successfully used to predict ligand poses in a variety of hGPCRs (Leguèbe et al, 2012;Marchiori et al, 2013;Sandal et al, 2015;Fierro et al, 2017;Capaldi et al, 2018;Fierro et al, 2019). Moreover, the Amber-based MM/CG poses improved significantly relative to those obtained by simple docking, especially for low resolution starting models (Schneider et al, 2020). However, the setup of such simulations has been time-consuming and system-dependent.…”
Section: Resultsmentioning
confidence: 99%
“…These include the adenosine 2A receptor in complex with caffeine (i.e., the example case of the webserver), the human bitter receptor 16 in complex with phenyl-β-D-glucopyranoside, the β2-adrenergic receptor with adrenaline, and the dopamine D3 receptor with eticlopride. The structures of these hGPCR/ligand complexes were either experimentally determined, taken from all-atom MD trajectories or predicted based on templates with decreasing resolution, up to extremely low sequence identity (<15%) (Schneider et al, 2020). Retrospective validation against available X-ray structures and mutagenesis data confirmed that the MM/CG approach can predict correct ligand poses and identify experimentally determined binding residues 2 (Schneider et al, 2020), regardless of the model resolution.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations